The orange shoes - Noble, Trinka Hakes (Sleeping Bear Press, 2007)
Delly Porter enjoys the feel of soft dirt beneath her feet as she walks to and from school, but after a classmate makes her feel ashamed of having no shoes she learns that her parents and others, too, see value in things that do not cost money.